Functional results of clavicle fractures in adults treated by open reduction and internal fixation using superior precontoured plate - Wani, M. Ahsan; Ganaie, Mushtaq Ahmed; Ul islam, Nuzhat; Rasool, Akther; Dar, Nisar Ahmed (International Surgery Journal, 2019)
Background: Observe results of open reduction and internal fixation of fractures of the clavicle in adults using pre-contoured superior clavicle locking plate. Methods: This study was prospective study carried out in the Govt Medical college Hospital Baramullah Kashmir Department of Orthopaedics from June 2014 to September 2016. A total of 25 patients with fresh fractures were treated with ORIF with a pre-contoured superior clavicle locking plate. Results: The mean age of patient was 30.08 years, males (64%), right clavicle frequently fractured (52%) Robinson type 2B1 configuraion. (44%) sustained their injury due to a road traffic accident. The average 6 month Quick DASH score was 0.82, whereas the mean constant score was 94.8 at final follow-up. The complications were superficial wound infection in (4%), mechanical pull-out of the plate in (8%), numbness below the incision area in (12%), symptomatic hardware in (4%), and non-union in (4%). Conclusions: There has been a resurgence of interest in operative treatment for fractures that are displaced, comminuted, or that display significant shortening. Operative treatment is beneficial to only a subset of patients, in whom functional expectations and fracture characteristics have both been taken into account before taking the final decision.